COMMUNITY SOCIO-ECONOMIC AND CULTURAL CONDITIONS IN THE OIL PALM PLANTATION DEVELOPMENT AREA (ELAEIS GUINEENSIS JACQ) PT. FARMING PRIMA MAKMUR IN ANDABIA VILLAGE, ANGGABERI DISTRICT, KONAWE REGENCY - Sarty Syarbiah; Usman Rianse; Ine Fausayana; Idrus Salam (Universitas Kristen Indonesia Toraja, 2022)
This study aims to determine the social, economic and cultural conditions of the community in the development area of the oil palm plantation of PT. Tani Prima Makmur (TPM) in Andabia Village, Anggaberi District, Konawe Regency. The population in this study were all people who grow oil palm independently and/or who work as laborers at the palm oil company PT Tani Prima Makmur (TPM) in Andabia Village, Anggaberi District, Konawe Regency, totaling 32 families. The sample determination in this study was carried out by census means that the entire population is sampled. The results of this study indicate that the social, economic and cultural conditions of the community in the development area of the PT Tani Prima Makmur (TPM) oil palm plantation in Andabia Village, Anggaberi District, Konawe Regency have had positive impacts in the form of opening new jobs and negative impacts in the form of environmental pollution.